PENYIDIKAN TINDAK PIDANA PENIPUAN JUAL BELI TANAH/LAHAN DI WIALAYAH HUKUM KEPOLISIAN SEKTOR BANGKO PUSAKO - Adil Sembiring; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Criminal acts of deception is one of the conventional crime continues to grow in the community, especially the deceptions sale of land in the Police Sector Bangko Pusako region which continued to increase from time to time. This is caused by the increasing population of the Indonesian people that the demand for land increased. Economic needs of the community that are not offset by an increase in welfare by the government is also a contributory factor on the criminal fraud cases this land purchase. In a criminal case the police have an important role as the spearhead of the laws are made in the form of acts of investigation. Investigation is a process of revealing the facts and the evidence for the occurrence of a crime and finding criminal suspects. Investigations were carried out police often encounter obstacles, it is motivated lack of public trust in the police and collisions that occur between the existing legal rules with the rule of law in the society.